Real-time imaging of oxidative and nitrosative stress in the liver of live animals for drug-toxicity testing - Shuhendler, Adam J; Pu, Kanyi; Cui, Lina; Uetrecht, Jack P; Rao, Jianghong (Nature biotechnology, 2014)
Semiconducting polymer nanoparticles are used to image toxic reactive oxygen and reactive nitrogen species in live mice. Current drug-safety assays for hepatotoxicity rely on biomarkers with low predictive power. The production of radical species, specifically reactive oxygen species (ROS) and reactive nitrogen species (RNS), has been proposed as an early unifying event linking the bioactivation of drugs to hepatotoxicity and as a more direct and mechanistic indicator of hepatotoxic potential. Here we present a nanosensor for rapid, real-time in vivo imaging of drug-induced ROS and RNS for direct evaluation of acute hepatotoxicity. By combining fluorescence resonance energy transfer (FRET) and chemiluminescence resonance energy transfer (CRET), our semiconducting polymer–based nanosensor simultaneously and differentially detects RNS and ROS using two optically independent channels. We imaged drug-induced hepatotoxicity and its remediation longitudinally in mice after systemic challenge with acetaminophen or isoniazid. We detected dose-dependent ROS and RNS activity in the liver within minutes of drug challenge, which preceded histological changes, protein nitration and DNA double-strand-break induction.